2016
DOI: 10.1103/physrevphyseducres.12.010125
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral self-regulation in a physics class

Abstract: This study examined the regulation of out-of-class time invested in the academic activities associated with a physics class for 20 consecutive semesters. The academic activities of 1676 students were included in the study. Students reported investing a semester average of 6.5 AE 2.9 h out of class per week. During weeks not containing an examination, a total of 4.3 AE 2.1 h was reported which was divided between 2.5 AE 1.2 h working homework and 1.8 AE 1.4 h reading. Students reported spending 7.6 AE 4.8 h pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…For example, in physics, tutorials, peer instruction (clicker questions with peer discussion), collaborative group problem solving with context-rich physics problems, POGIL (process-oriented guided-inquiry learning) activities, etc. have been found effective in helping students learn [64][65][66][67][68][69][70][71][72][73][74][75][76]. Furthermore, several validated conceptual standardized surveys have been developed [83] to assess students' conceptual understanding of various physics topics.…”
Section: A Factors 1 and 2: Internal Characteristics Of Learning Toomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in physics, tutorials, peer instruction (clicker questions with peer discussion), collaborative group problem solving with context-rich physics problems, POGIL (process-oriented guided-inquiry learning) activities, etc. have been found effective in helping students learn [64][65][66][67][68][69][70][71][72][73][74][75][76]. Furthermore, several validated conceptual standardized surveys have been developed [83] to assess students' conceptual understanding of various physics topics.…”
Section: A Factors 1 and 2: Internal Characteristics Of Learning Toomentioning
confidence: 99%
“…In the past few decades, physics education researchers have investigated the challenges students face in learning physics and developed research-based instructional tools to improve student understanding of physics and their problem-solving and reasoning skills [64][65][66][67][68][69][70][71][72][73][74][75][76]. Indeed, effective pedagogies and learning tools build on students' prior knowledge and skills and provide appropriate coaching and support to help all students learn [77][78][79][80][81].…”
Section: Introductionmentioning
confidence: 99%
“…Of the two publications in Physical Review PER that mentioned hierarchical linear model, the first mentioned HLM as a possible method of analysis but did not use it [12]. The second publication stated that they performed both HLM and linear regression, but because they had similar results they only included the linear regression results in the publication [13]. Independent of our literature search, we identified two Physical Review PER articles [14,15] that used HLM but did not show up in our search because they referred to HLM using the less common nomenclature of hierarchical-model analysis and hierarchical linear regression.…”
Section: Motivationmentioning
confidence: 99%
“…On the other hand, Kortemeyer found that students who tended to make physics-related comments on an online course discussion board had higher course grades and concept test scores compared to students who tended to make solution-oriented comments [11]. Stewart and colleagues found that students who earned high end-of-course grades were better able to self-regulate by changing their exam preparation time in reaction to their progress in the course compared to those who earned low end-of-course grades [12,13]. We expect that such behaviors may play an even more significant role in determining student success in studio-mode courses, which require active engagement of students both inside and outside of class.…”
Section: Introductionmentioning
confidence: 99%